Violence and HIV/STI Vulnerability Among Female Sex Workers in Delhi's Red Light Area (International Journal of Food and Nutritional Sciences, 2022)
Introduction: According to the World Health Organization (WHO), violence is defined as the intentional use of physical force or power against a group or community, resulting in or having a high likelihood of resulting in injury. This study focuses on various types of violence, including sexual violence (perpetrated by clients, police, procurers, family members, or intimate partners), physical violence, and verbal abuse. Most violence against sex workers is a manifestation of gender inequality and discrimination directed at women.